“Allah will decide my life and death”: Religion and spirituality among populations at risk for HIV in Malaysia - Shaw, Stacey Anne; Cornwell, Olivia; Lim, Sin How; Saifi, Rumana; Ung, Lik Teng; Kamarulzaman, Adeeba (Taylor & Francis, 2018)
We examined the influence of religion and spirituality on HIV risk contexts through in-depth interviews with men who have sex with men (n = 10) and female commercial sex workers (n = 10) in Malaysia. Using a grounded theory approach, five themes emerged from the interviews: (a) religion encourages caring for health, (b) health is influenced by a higher power, (c) prayer is a conduit to health assistance, (d) stigma is compounded by religion but it does not limit one’s spirituality, and (e) religion is not but should be incorporated into HIV campaigns. Incorporation of spirituality in service provision and addressing stigma is warranted.